VIDEO GAME SEBAGAI TERAPI KECEMASAN ANAK PRE OPERASI - Sepi Prabangkoro, Gondo; Very Anto, Yuni (Jurnal Media Ilmu Kesehatan, 2013)
Background: Anxiety is a dominant response in children undergoing treatment prior to operation. When anxiety is not soon resolved it will affect physiological and psychological condition of children leading uncooperative behavior. Playing therapy intervention is given in efforts to minimize anxiety in children before operation. One of playing therapy interventions relevant with age of school children is video game playing therapy. Objective: The study aimed to identify effect of video game playing therapy to anxiety of preoperative school children at Melati surgery ward of Panembahan Senopati Hospital Bantul. Method: The study used pre experimental method and pre test and post test design of one group  without control. Samples consisted of 14 school children taken through purposive sampling. Data were collected before and after video game playing therapy and anxiety instrument Zung Self Rating Anxiety Scale (ZSRAS) in check list sheet and analyzed using Wilcoxon signed rank test with ? = 0.05. Result: The result of Wilcoxon signed rank test showed significance of p-value = 0.001 < ? = 0.05. This showed there was effect of video game playing therapy to level of anxiety in preoperative school children at Melati Surgey Ward of Panembahan Senopati Bantul. Conlusion : There was decrease of anxiety in preoperative school children after intervention of video game playing therapy. Keywords : Playing therapy, anxiety, school children